2015
DOI: 10.1111/ajgw.12191
|View full text |Cite
|
Sign up to set email alerts
|

Differential fruitset between grapevine cultivars is related to differences in pollen viability and amine concentration in flowers

Abstract: Background and Aims Reproductive capacity among grapevine cultivars varies considerably and impacts yield. Bioactive amines are reported to be involved in many aspects of plant reproductive physiology. We aimed to examine the association between the reproductive performance of cultivars and the concentration of amines in the reproductive organs. Methods and Results The reproductive performance of Shiraz, Merlot and Cabernet Sauvignon was assessed by determining fruitset, coulure index, millerandage index, poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
(70 reference statements)
2
16
0
Order By: Relevance
“…A mean value of 3.6 was reported by Dry et al[9] for 10 varieties, a lower value than the one found here, likely because of the large number of LGOs found in that study(48.7 LGOs, we found 11.8). Baby et al[23] also found a high Coulure index in Cabernet Sauvignon (5.5), and lower in Merlot (4.2 vs. 5.1 here) and Shiraz (3.3 vs. 1.3 in this work).…”
supporting
confidence: 69%
See 3 more Smart Citations
“…A mean value of 3.6 was reported by Dry et al[9] for 10 varieties, a lower value than the one found here, likely because of the large number of LGOs found in that study(48.7 LGOs, we found 11.8). Baby et al[23] also found a high Coulure index in Cabernet Sauvignon (5.5), and lower in Merlot (4.2 vs. 5.1 here) and Shiraz (3.3 vs. 1.3 in this work).…”
supporting
confidence: 69%
“…Instead, counting the number of flower caps or calyptras (fused petals) collected in a bag is a non-destructive valid method, because each flower releases one calyptra at blooming [9,17,18,23], which can be delayed. On the other hand, new image analyses tools have been recently developed for estimating the number of flowers from 2D images of the inflorescences, although they have usually been tested in a limited set of varieties [28][29][30][31][32][33].…”
Section: In Many Cases Seedless Berries Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been suggested that fruitset differences between three cultivars, Shiraz, Merlot and Cabernet Sauvignon, are attributable to differences in pollen viability and in the concentration of diverse amines (e.g. diaminopropane and phenylethylamine) in flowers, which can inhibit pollen tube growth and therefore interrupt the normal fertilisation process (Baby et al ).…”
Section: Which Factors Affect Bunch Compactness?mentioning
confidence: 99%